The influence of plant size and fertilization on catkin production in birch (Betula pubescens Ehrh.) - Julia Carolina Bos 1996- (2018)
Downy birch Betula pubescens Ehrh. is the only tall growing native birch species in Iceland. Around the time of the settlement, birch woodlands used to cover large areas of Iceland, but today only little is left. Regeneration of birch is a key process in woodland expansion and is important for land reclamation and restoration. Success of natural regeneration depends largely on seed production and seed establishment. Therefore, information about factors influencing these processes is of value. Plant seed production is affected by a number of factors, including nutrient availability, moisture supply, weather conditions, plant density and predation. The main objective of this project is to assess the effects of plant size and fertilization on seed production, using data from experiments conducted at two research sites in North and South Iceland in 1992-1994: Hálsmelar and Gunnlaugsskógur. A positive correlation was found between plant size and catkin production. Youngest catkin producing plants were on average 32 to 97 centimetres long and their estimated age was 6 to 16 years. Data further suggested that small size of plants might be a limiting factor in reproductive maturity as percentage of catkin bearing plants increased with plant size. High and low fertilizer treatments increased catkin production in Gunnlaugsskógur, but not in Hálsmelar. However, fertilization did increase plant growth at both sites and could therefore possibly increase catkin production over a longer period of time.